If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1.5(14X + 2) = 3(2 + -3X) Reorder the terms: 1.5(2 + 14X) = 3(2 + -3X) (2 * 1.5 + 14X * 1.5) = 3(2 + -3X) (3 + 21X) = 3(2 + -3X) 3 + 21X = (2 * 3 + -3X * 3) 3 + 21X = (6 + -9X) Solving 3 + 21X = 6 + -9X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '9X' to each side of the equation. 3 + 21X + 9X = 6 + -9X + 9X Combine like terms: 21X + 9X = 30X 3 + 30X = 6 + -9X + 9X Combine like terms: -9X + 9X = 0 3 + 30X = 6 + 0 3 + 30X = 6 Add '-3' to each side of the equation. 3 + -3 + 30X = 6 + -3 Combine like terms: 3 + -3 = 0 0 + 30X = 6 + -3 30X = 6 + -3 Combine like terms: 6 + -3 = 3 30X = 3 Divide each side by '30'. X = 0.1 Simplifying X = 0.1
| t(9t+1)=8 | | 6(5-4f)=26 | | 4x+40+32y=0 | | 2*8+22c=32 | | 3x+23/5+x+10/7=9 | | 2(5z-3)-4(z-2)= | | 12x-4y+16=0 | | .18y+.02(y+9000)=780 | | -.10(58)+.65x=.05(x-20) | | 3(12-2y)+2y=8 | | 2x^2-37x+66=0 | | -8-12y+5=15 | | 4q-q-(2q-3)= | | 3x+1x=15 | | 3x+1x=20 | | 3x+1x=1 | | 7(5-3x)+5(5x-3)= | | 4x^2-2x=80 | | (9y+5)-(7y-3)= | | 66+17y=17 | | 5x=x^2+6 | | x+2x+3x+3=15 | | 2(8+2c)=32 | | 30+5t=80 | | 12x-8=3x+28 | | x+2+3x+3=15 | | 2(5y+6)-4(y-8)= | | 2x^2+2=2 | | n-3/4+n+5/7=5/14 | | 0.5x+x=x | | 0.5x+x=y | | 0.5x+x=1.5x |